Factors affecting interactions between prion protein isoforms. (August 2002) - Caughey, B.; Baron, G. S.
Abstract : Interactions between normal, protease-sensitive prion protein (PrP-sen or PrP c ) and its protease-resistant isoform (PrP-res or PrP sc ) are critical in transmissible spongiform encephalopathy (TSE) diseases. To investigate the propagation of PrP-res between cells we tested whether PrP-res in scrapie brain microsomes can induce the conversion of PrP-sen to PrP-res if the PrP-sen is bound to uninfected raft membranes. Surprisingly, no conversion was observed unless the microsomal and raft membranes were fused or PrP-sen was released from raft membranes. These results suggest that the propagation of infection between cells requires transfer of PrP-res into the membranes of the recipient cell. To assess potential cofactors in PrP conversion, we used cell-free PrP conversion assays to show that heparan sulphate can stimulate PrP-res formation, supporting the idea that endogenous sulphated glycosaminoglycans can act as important cofactors or modulators of PrP-res formation in vivo . In an effort to develop therapeutics, the antimalarial drug quinacrine was identified as an inhibitor of PrP-res formation in scrapie-infected cell cultures. Confirmation of the latter result by others has led to the initiation of human clinical trials as a treatment for Creutzfeldt-Jakob disease. PrP-res formation can also be inhibited using a variety of other types of small molecule, specific synthetic PrP peptides, and an antiserum directed at the C-terminus of PrP-sen. The latter results help to localize the sites of interaction between PrP-sen and PrP-res. Disruption of those interactions with antibodies or peptidomimetic drugs may be an attractive therapeutic strategy. The likelihood that PrP-res inhibitors can rid TSE-infected tissues of PrP-res would presumably be enhanced if PrP-res formation were reversible. However, our attempts to measure dissociation of PrP-sen from PrP-res have failed under non-denaturing conditions. Finally, we have attempted to induce the spontaneous conversion of PrP-sen into PrP-res using low concentrations of detergents. A conformational conversion from α-helical monomers into high-β-sheet aggregates and fibrils was induced by low concentrations of the detergent sarkosyl; however, the aggregates had neither infectivity nor the characteristic protease-resistance of PrP-res.